Effects of pre-marital sexual relationships and teenage pregnancy on academic performance among adolescent-students in Yaba LCDA of Lagos-Nigeria - Kehinde Kamolideen Lawal; Opeyemi Ogunyomi; Oginni Sunday Folorunso; Ogunsesan Bilkis Oyebola; Babatunde Oluwaseun T. (International Journal on Education Insight, 2026)
Teenage pregnancy, which is often the direct result of premarital sexual relationships, is a significant concern, especially in Nigeria, where the consequences of early childbearing are felt in the academic performance. Thus, this study examined how adolescent pupils in Lagos State's Yaba Local Council Development Area (LCDA) performed academically in relation to premarital sexual encounters and teenage pregnancy. A descriptive survey design was adopted for the study with a sample of 97secondary school students. Pearson-Product Moment Correlation and Chi-Square statistical methods were used to assess three research hypotheses at the 0.05 level of significance. The results showed that premarital sexual relationships and academic achievement are significantly correlated among adolescent-students in Yaba LCDA, teenage pregnancy has no significant influence on school attendance among adolescent-students in Yaba LCDA, and there is a significant influenceof parental involvement on the prevention of premarital sexual relationships adolescent-students in Yaba LCDA. Based on these findings, the study recommended that schools should integrate well-structured and age-appropriate sexual and reproductive health education into their curricula, parents should be actively involved in their children's lives by fostering open and non-judgmental communication about relationships, sexuality, and academic aspirations, schools should establish counselling and mentorship programs to support students, particularly teenage mothers, in managing both academic and personal responsibilities, and that schools and community organizations should create peer mentorship programs where older students or trained peer educators can guide younger ones on making informed life choices.